The triple layered business model canvas: A tool to design more sustainable business models - Joyce, Alexandre; Paquin, Raymond L. (Journal of Cleaner Production, 2016)
The Triple Layered Business Model Canvas is a tool for exploring sustainability-oriented business model innovation. It extends the original business model canvas by adding two layers: an environmental layer based on a lifecycle perspective and a social layer based on a stakeholder perspective. When taken together, the three layers of the business model make more explicit how an organization generates multiple types of value - economic, environmental and social. Visually representing a business model through this canvas tool supports developing and communicating a more holistic and integrated view of a business model; which also supports creatively innovating towards more sustainable business models. This paper presents the triple layer business model canvas tool and describes its key features through a re-analysis of the Nestle Nespresso business model. This new tool contributes to sustainable business model research by providing a design tool which structures sustainability issues in business model innovation. Also, it creates two new dynamics for analysis: horizontal coherence and vertical coherence. (C) 2016 Elsevier Ltd. All rights reserved.
Place: Oxford Publisher: Elsevier Sci Ltd WOS:000382792900125
Keywords: Commerce; Durabilité; Développement durable; Développement technologique; Innovation durable; Modèle; Réservé UdeM; Triple layered business model canvas